Catalyst as well as preparation method and application thereof in ethylene polymerization reaction
By using clay sepiolite mesoporous material as a carrier and combining it with magnesium and titanium components, a highly active ethylene polymerization catalyst with high packing density and narrow molecular weight distribution was prepared. This solved the problems of low catalyst activity and poor particle morphology in the existing technology, and improved the efficiency and product quality of ethylene polymerization.
Patent Information
- Application Number
- CN202411640691.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2026-05-15
AI Technical Summary
Existing Ti/Mg composite Ziegler-Natta catalysts suffer from low catalytic activity, poor catalyst particle morphology, and wide polymer molecular weight distribution in ethylene polymerization, especially the poor aggregation and flowability of ordered mesoporous materials.
Using clay sepiolite mesoporous material as a carrier, combined with magnesium and titanium components, a catalyst was formed through a specific preparation method, including the contact reaction of magnesium compounds, alcohol ether compounds and titanium compounds and spray drying, to prepare a catalyst with high specific surface area and narrow pore size distribution.
This improved catalytic activity, yielded polymers with high packing density and narrow molecular weight distribution, and enhanced catalyst flowability and particle morphology.
Smart Images

Figure CN122037019A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalysts for the preparation of olefin polymers, and more specifically, to a catalyst, a method for its preparation, and its application in ethylene polymerization. Background Technology
[0002] Currently, the Ziegler-Natta catalyst system based on Ti / Mg composites still dominates the industrial production of polyethylene. Technicians in this field are dedicated to developing effective methods to achieve two main goals: firstly, to obtain catalysts with sufficiently high polymerization activity, ensuring high efficiency in the production process while minimizing residue in the polymer; and secondly, to obtain polymer particles with uniform distribution, near-spherical morphology, and low content of fine polymer powder, facilitating long-term continuous operation of industrial plants. To obtain favorable particle morphology, catalysts are often prepared using a supported method, impregnating the active catalyst component onto a particulate support material, such as porous inorganic support materials like silica or organic particulate support materials.
[0003] Therefore, there is a need for a catalyst suitable for ethylene polymerization that not only has high catalytic activity but also good catalyst particle morphology, so that the prepared polymer powder has a high polymer packing density and a narrow polymer molecular weight distribution.
[0004] In 1992, Mobile synthesized a mesoporous material (Beck JS, Vartuli JC, Roth WJ, et al. J. Am. Chem. Soc., 1992, 114(27): 10834-10843). This mesoporous material has a high specific surface area, regular pore structure, and narrow pore size distribution, which has attracted great attention for its application in catalysis, separation, medicine and other fields. In 1998, Zhao Dongyuan et al. synthesized a new material - the mesoporous material SBA-15 (DYZhao, JLFeng, QSHuo, et al. Science). 279(1998)548-550), this material has a highly ordered cubic single crystal mesoporous material with pore size (6-30nm), large pore volume (1.0cm3 / g), thick pore walls (4-6nm) maintaining high mechanical strength and good catalytic adsorption performance; Zhao Dongyuan, Yu Chengzong, and Yu Yonghao invented a method for preparing mesoporous molecular sieve support material (CN1113811C), this mesoporous material, as a multiphase reaction catalyst support, can easily achieve the separation of catalyst and product (Wight, AP; Davis, MEChem.Rev.2002,102,3589; De Vos, DE; Dams, M.; Sels, BF; Jacobs, PAChem.Rev.2002,102,3615.).
[0005] The conventional ordered mesoporous material SBA-15 has a rod-like microstructure, which results in poorer flowability compared to materials with a spherical microstructure. Furthermore, its large specific surface area and high pore volume give it a strong ability to absorb water and moisture, further exacerbating the aggregation of rod-shaped ordered mesoporous materials and causing inconvenience in their storage, transport, post-processing, and application. In contrast, the geometric shape of microspheres offers significant advantages in reducing powder aggregation and improving its flowability.
[0006] Therefore, researching and developing a catalyst is of great significance. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of existing technologies in the preparation of polyolefin catalysts, such as the limitations imposed by factors like the pore structure of the support and the solubility of the component to be supported, resulting in a low effective loading of the active component on the support, which in turn leads to low catalytic activity of supported polyolefin catalysts prepared from existing supported polyolefin catalyst supports. This invention provides a catalyst, its preparation method, and its application in ethylene polymerization. This catalyst exhibits high catalytic activity when used for homopolymerization or copolymerization of ethylene, and the resulting polymer has a high bulk density, a small melt flow ratio, and a narrow molecular weight distribution.
[0008] To achieve the above objectives, the first aspect of the present invention provides a catalyst comprising a support and an active component loaded on the support, wherein the support is a clay sepiolite mesoporous material support, the active component is a magnesium component and a titanium component, and the support has an average particle diameter of 20-50 micrometers, a specific surface area of 150-600 square meters / gram, a pore volume of 0.5-1.5 milliliters / gram, and most probable pore sizes of 2-4, 5-15, and 10-40 nanometers, respectively.
[0009] A second aspect of the present invention provides a method for preparing a catalyst, wherein the preparation method includes:
[0010] (1) Magnesium compounds, alcohol ether compounds and ether compounds are reacted to form a magnesium compound solution;
[0011] (2) The magnesium compound solution is reacted with the clay sepiolite mesoporous material carrier in a first contact reaction to obtain a slurry;
[0012] (3) The slurry is reacted with the titanium compound in a second contact reaction to obtain the masterbatch to be sprayed;
[0013] (4) The masterbatch to be sprayed is spray-dried to obtain the catalyst.
[0014] A third aspect of the present invention provides a catalyst prepared by the preparation method described above.
[0015] A fourth aspect of the present invention provides the application of the aforementioned catalyst in the polymerization reaction of ethylene.
[0016] The beneficial effects of the above-mentioned technical solution are as follows: the clay sepiolite mesoporous material carrier used in this invention has a high specific surface area and pore structure, which can effectively improve the loading of active centers. It has high catalytic activity when used for ethylene homopolymerization or copolymerization. Furthermore, when combined with specific raw material magnesium compound solution, titanium compound, alcohol ether compound and ether compound, the polymer powder prepared has a high packing density and the molecular weight distribution of the prepared polymer is narrow. Attached Figure Description
[0017] Figure 1 This is the XRD pattern of the spherical sepiolite-clay mineral composite carrier (MBQGJHP);
[0018] Figure 2 This is a scanning electron microscope (SEM) image of the microstructure of a spherical sepiolite-clay mineral composite carrier (MBQGJHP).
[0019] Figure 3This is a scanning electron microscope (SEM) image of a spherical sepiolite clay mineral composite carrier (MBQGJHP-HP) loaded with phosphoric acid via spray drying.
[0020] Figure 4 This is a magnified SEM image of the microstructure of a spherical sepiolite-clay mineral composite carrier (MBQGJHP) loaded with phosphoric acid via spray drying.
[0021] Figure 5 This is the pore size distribution curve of the spherical sepiolite composite carrier (MBQGJHP). Detailed Implementation
[0022] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0023] As previously stated, the first aspect of the present invention provides a catalyst comprising a support and an active component loaded on the support, wherein the support is a clay sepiolite mesoporous material support, the active component is a magnesium component and a titanium component, and the support has an average particle diameter of 20-50 micrometers, a specific surface area of 150-600 square meters / gram, a pore volume of 0.5-1.5 milliliters / gram, and most probable pore sizes of 2-4, 5-15, and 10-40 nanometers, respectively.
[0024] According to the present invention, the clay-sepiolite mesoporous material carrier has a two-dimensional hexagonal channel structure. The average particle diameter of the spherical sepiolite-clay mineral composite carrier is preferably 20-40 micrometers; the specific surface area is 180-600 m² / g, preferably 229-585 m² / g; the pore volume is 0.8-1.3 mL / g, preferably 0.9-1 mL / g; and the most probable pore sizes are preferably 3-4, 7-15, and 30-40 nm, respectively. Under these conditions, not only can satisfactory catalytic effects be obtained, but costs can also be reduced. At the same time, the mesoporous material can be guaranteed to have the advantages of large pore size, large pore volume, and large specific surface area, which is more conducive to the good dispersion of magnesium and / or titanium active components on the surface of the mesoporous material, thereby ensuring that the polyolefin catalyst prepared therefrom has excellent catalytic performance.
[0025] The inventors of this invention have discovered that combining the advantages of microspheres, ordered mesoporous materials, and sepiolite clay minerals can retain the characteristics of ordered mesoporous materials, such as high specific surface area, large pore volume, large pore size, and narrow pore distribution, while reducing the aggregation of ordered mesoporous materials and increasing their fluidity. At the same time, the introduction of inexpensive natural clay mineral materials reduces the cost of the materials. This will provide a better platform for the application of ordered mesoporous materials and expand their application fields.
[0026] Sepiolite is a magnesium-rich fibrous silicate clay mineral and one of the most widely used and rapidly expanding mineral resources in modern times. The development of novel catalyst supports from natural clay minerals has always been a focus of research. my country has relatively abundant sepiolite resources, making its development as a catalyst support not only of research value but also of great practical significance. However, sepiolite suffers from drawbacks such as weak surface acidity, small channels, poor thermal stability, and the destructive effect of water vapor on the molecular sieve structure. Therefore, modifying natural sepiolite is essential for its application as a catalyst support. This study utilizes the modifiability of sepiolite to investigate its performance as a catalyst support. Since sepiolite possesses a large potential specific surface area, and its catalytic activity is directly proportional to its surface area, increasing the internal and external surface areas of sepiolite can characterize its performance as a catalyst support.
[0027] According to the present invention, based on the total weight of the catalyst, the content of the clay sepiolite mesoporous material carrier is 20-90% by weight, preferably 20-70% by weight; the content of the magnesium component, calculated as elemental magnesium, is 1-50% by weight, preferably 1-30% by weight; and the content of the titanium component, calculated as elemental titanium, is 1-50% by weight, preferably 1-30% by weight.
[0028] According to the present invention, the carrier comprises a mesoporous material and clay sepiolite loaded on the mesoporous material, and the content of the mesoporous material is 1-90% by weight and the content of the clay sepiolite is 1-10% by weight, based on the total weight of the carrier; preferably, the content of the mesoporous material is 5-90% by weight and the content of the clay sepiolite is 5-10% by weight, based on the total weight of the carrier.
[0029] According to the present invention, the method for preparing the carrier includes:
[0030] (a) In the presence of a template agent, trimethylpentane and ethanol, tetramethoxysilane was first contacted with an acidic aqueous solution, and the mixture obtained after the first contact was crystallized, washed and filtered to obtain mesoporous material filter cake No. 1; hexadecyltrimethylammonium bromide and silicon source were added to an ammonia aqueous solution and filtered to obtain mesoporous material filter cake, and the filter cake was washed to obtain mesoporous material filter cake No. 2;
[0031] (b) The water glass was brought into contact with the inorganic acid for a second time, and the mixture obtained after the second contact was washed and filtered to obtain a silica gel filter cake;
[0032] (c) Ball mill the No. 1 mesoporous material filter cake, the No. 2 mesoporous material filter cake, the silica gel filter cake and the sepiolite clay mineral together;
[0033] (d) The solid powder obtained from (c) is prepared into a slurry in the presence of deionized water and then spray-dried; and the spray-dried product is heated to remove the template agent, thereby obtaining a clay sepiolite mesoporous material carrier.
[0034] According to the present invention, in step (a), the type of template agent is not particularly limited. Preferably, the template agent can be a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, which can be commercially available (e.g., it can be purchased from Aldrich under the trade name P123, with the molecular formula EO). 20 PO 70 EO 20 It can also be prepared using various existing methods.
[0035] The acidic aqueous solution can be any of the acidic aqueous solutions commonly used in the art, for example, it can be an aqueous solution of at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrobromic acid, preferably an aqueous solution of hydrochloric acid.
[0036] The amount of the acidic aqueous solution is not particularly limited and can vary within a wide range. Preferably, the pH value of the mixture is 1-6.
[0037] The ammonia solution is an alkaline aqueous solution.
[0038] According to the present invention, in step (a), the amount of the acidic aqueous solution used is such that the pH value is 1-6.
[0039] In this invention, the silicon source can be any silicon source conventionally used in the art, preferably at least one of tetraethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol, more preferably tetraethyl orthosilicate.
[0040] In this invention, the amounts of the template agent and the silicon source can vary within a wide range. In a preferred embodiment of this invention, the molar ratio of the template agent and the silicon source is 1:(10-90), preferably 1:(50-75).
[0041] According to a preferred embodiment of the present invention, the process of mixing and contacting the silicon source with the acidic aqueous solution in the presence of the template agent includes: adding the template agent triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123 to the hydrochloric acid aqueous solution at a molar ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123:water:hydrogen chloride = 1:9000-15000:100-500, stirring at 25-60°C until dissolved, and then adding the silicon source tetraethyl orthosilicate to the above-obtained solution at a molar ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123:tetraethyl orthosilicate = 1:50-75, and stirring at 25-60°C for more than 25 minutes.
[0042] In a preferred embodiment of the present invention, the crystallization conditions include a temperature of 90-180°C and a time of 10-40 hours. According to a preferred embodiment, the crystallization is carried out by a hydrothermal crystallization method. To ensure that a mesoporous molecular sieve material with a sufficiently large pore size is obtained, the crystallization conditions are further preferably a temperature of 130-180°C.
[0043] Preferably, the filtration process may include: after filtration, repeatedly washing with deionized water (the number of washings may be 2-10), and then performing filtration.
[0044] Preferably, the drying can be carried out in a drying oven, and the drying conditions may include: a temperature of 110-150°C and a time of 3-6 hours.
[0045] According to the present invention, in step (a), hexadecyltrimethylammonium bromide and tetraethyl orthosilicate are added to an ammonia solution at a molar ratio of tetraethyl orthosilicate: hexadecyltrimethylammonium bromide: ammonia (25%): deionized water = (1:0.1-1:0.1-5:100-200) (actual ratio 1:0.37:2.8:142). The mixture is stirred at 25-100°C until dissolved. The solution is filtered to obtain a mesoporous material filter cake. The filter cake is washed until the pH is 7 to obtain mesoporous material filter cake No. 2.
[0046] According to the present invention, preferably, in step (a), tetramethoxysilane is mixed with an acidic aqueous solution in the presence of a template agent, trimethylpentane, and ethanol, followed by a first contact. In this invention, the amount of ethanol used is 1-2 grams relative to 1 gram of template agent to ensure complete dissolution of the template agent; the amount of trimethylpentane used is 5-10 grams relative to 1 gram of template agent, and the amount of tetramethoxysilane used is 2-8 grams. Furthermore, the conditions for the mixing contact include: a temperature of 25-60°C, a time of 25 minutes or more, and a pH of 1-6. To further facilitate uniform mixing of the substances, according to a preferred embodiment of the present invention, the mixing contact is carried out under stirring conditions.
[0047] According to the present invention, in step (a), the first contact temperature is 10-60°C and the contact time is 10-72 hours; the crystallization temperature is 30-150°C and the crystallization time is 10-72 hours.
[0048] According to the present invention, in step (b), the second contact temperature is 10-60°C and the contact time is 1-5 hours; the inorganic acid is one or more of sulfuric acid, nitric acid, and hydrochloric acid, and the pH value of the inorganic acid is 2-4.
[0049] According to the present invention, in step (b), water glass with a concentration of 15% by weight and sulfuric acid solution with a concentration of 12% by weight are reacted to a sufficient ratio of water glass to sulfuric acid of 5-8:1.
[0050] According to the present invention, in step (c), the weight ratio of the sepiolite clay mineral to the No. 1 mesoporous material filter cake, the No. 2 mesoporous material filter cake, and the silica gel filter cake is (1-30):(1-30):(1-30):20, preferably (1-20):(1-10):(1-10):20.
[0051] According to the present invention, in step (c), the specific operation method and conditions of the ball milling treatment are based on not damaging or substantially not damaging the pore structure of the mesoporous material. Those skilled in the art can select various suitable conditions to implement the present invention based on the above principles. Specifically, the ball milling treatment can be carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the grinding jar; for a grinding jar of 50-150 mL, 20-80 grinding balls can usually be used; the material of the grinding balls can be agate, polytetrafluoroethylene, etc., preferably agate. The ball milling conditions include: the rotational speed of the grinding balls can be 300-500 r / min, the temperature inside the grinding jar can be 15-100℃, and the ball milling time can be 0.1-100 hours. In a preferred embodiment, step (c) is carried out under nitrogen protection. Dichlorodimethylsilane may be added during the ball milling process to further remove hydroxyl groups from the surface of the mesoporous carrier. The ball milling conditions result in an average particle diameter of 0.5-10 μm for the clay sepiolite mesoporous material carrier obtained by ball milling.
[0052] According to the present invention, in step (d), the template removal process includes: dissolving the mesoporous material powder in deionized water and spray drying it at 200-300°C and a rotation speed of 10000-12000 r / min; calcining the product obtained after spray drying in a muffle furnace to remove the template agent, wherein the template agent removal temperature is 300-600°C and the time is 10-80 hours.
[0053] According to the present invention, in step (d), in order to remove the hydroxyl groups and residual moisture from the clay sepiolite mesoporous material carrier, a thermal activation treatment is required before loading the metal component onto the clay sepiolite mesoporous material carrier. The conditions for the thermal activation treatment may include: calcining the clay sepiolite mesoporous material carrier at a temperature of 300-900°C for 7-10 hours in the presence of nitrogen.
[0054] A second aspect of the present invention provides a method for preparing a catalyst, wherein the preparation method includes:
[0055] (1) Magnesium compounds, alcohol ether compounds and ether compounds are reacted to form a magnesium compound solution;
[0056] (2) The magnesium compound solution is reacted with the clay sepiolite mesoporous material carrier in a first contact reaction to obtain a slurry;
[0057] (3) The slurry is reacted with the titanium compound in a second contact reaction to obtain the masterbatch to be sprayed;
[0058] (4) The masterbatch to be sprayed is spray-dried to obtain the catalyst.
[0059] According to the present invention, the magnesium compound can be selected from a wide range, and in a preferred embodiment of the present invention, the magnesium compound is selected from the formula Mg(OR1). m Cl 2-m One or more of the compounds shown, wherein R1 is C2-C 20 Alkyl or C3-C 20 Cyclic hydrocarbon groups, preferably C2-C 10 The alkyl group, 0 ≤ m ≤ 2; preferably, the magnesium compound is selected from at least one of magnesium diethoxy, magnesium dipropoxy, magnesium dibutoxy, magnesium dioctyloxy, and magnesium dichloride.
[0060] According to the present invention, the titanium compound can be selected from a wide range. In a preferred embodiment of the present invention, the titanium compound is selected from one or more titanium halides, preferably titanium chloride and / or titanium bromide, and more preferably titanium trichloride and / or titanium tetrachloride.
[0061] According to the present invention, the alcohol ether compound can be selected from a wide range. In a preferred embodiment of the present invention, the alcohol ether compound is selected from one or more of the lower carbon alcohol ethers of ethylene glycol and the lower carbon alcohol ethers of propylene glycol, preferably from one or more of propylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol monopropyl ether, propylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monobutyl ether, and propylene glycol monopropyl ether.
[0062] According to the present invention, the ether compound can be selected from a wide range. In a preferred embodiment of the present invention, the ether compound is selected from one or more of anisole, phenethyl ether, propyl ether, butyl ether, isopropyl ether, isobutyl ether, 1,4-dioxane, tetrahydrofuran, methyltetrahydrofuran, ethylene oxide, 1,2-epoxypropane, 1,2-epoxybutane, cis-2,3-epoxybutane, trans-2,3-epoxybutane, 9,9-(dimethoxymethyl)fluorene, isopentyl ether, and pentyl ether. In the present invention, one or more of the above-mentioned ether compounds having 3-5 carbon atoms, such as tetrahydrofuran and / or methyltetrahydrofuran, are preferred, and tetrahydrofuran is more preferred.
[0063] According to the present invention, the amount of the clay sepiolite mesoporous material carrier is 0.01-1 mol, preferably 0.02-0.9 mol, more preferably 0.03-0.8 mol; the amount of the titanium compound is 1-15 mmol, preferably 2-14 mmol, more preferably 3-10 mmol; the amount of the magnesium compound is 1-100 mmol; the amount of the ether compound is 1-10 mol; and the amount of the alcohol ether compound is 1-15 mmol.
[0064] According to the present invention, in step (1), the magnesium compound, alcohol ether compound and ether compound are reacted with each other at 30-100°C, preferably at 40-80°C. Higher temperatures are advantageous for the reaction. The reaction is carried out under stirring conditions. The reaction time depends on the properties of the reactants and the operating conditions. The reaction time is required to obtain a transparent solution. The required reaction time is 1-20 hours, preferably 2-10 hours, until a transparent solution is formed.
[0065] According to the present invention, in step (2), the transparent solution obtained in step (1) is reacted with the clay sepiolite mesoporous material carrier at 0-100°C, preferably 0-80°C; the mixing time is generally selected from 30 minutes to 10 hours, preferably 0.5-4 hours. The reaction in step (2) includes the reaction between the magnesium compound obtained in step (1) and the surface groups of the clay sepiolite mesoporous material carrier, and the magnesium compound component enters the pores of the clay sepiolite mesoporous material carrier by the capillary pressure of the pore structure of the carrier.
[0066] According to the present invention, in step (3), the suspension obtained in step (2) is reacted with titanium halide at a reaction temperature of 0-80°C, preferably 20-70°C; and the reaction time is 0.5-10h, preferably 0.5-5h, to obtain the masterbatch to be sprayed.
[0067] According to the present invention, in step (4), the conditions for spray drying are as follows: the spray drying is carried out under a protective atmosphere, the inlet temperature is 100-200℃, preferably 120-160℃, the outlet temperature is 60-130℃, preferably 90-115℃, and the carrier gas flow rate is 200-600L / h.
[0068] The protective atmosphere in this invention is nitrogen and / or an inert gas.
[0069] A third aspect of the present invention provides a catalyst prepared by the preparation method described above.
[0070] A fourth aspect of the present invention provides the application of the aforementioned catalyst in the polymerization reaction of ethylene.
[0071] According to the present invention, the ethylene polymerization reaction can be homopolymerization of ethylene or copolymerization of ethylene with α-olefins. The polymerization reaction conditions are not particularly limited and can be olefin polymerization conditions commonly used in the art. The α-olefin can be at least one selected from propylene, butene, pentene, hexene, octene, and 4-methylpentene-1.
[0072] In their research on the preparation of polyolefins from olefin monomers, the inventors of this invention discovered that the clay sepiolite mesoporous material support in the polyolefin catalyst prepared by the method of this invention, due to its special two-dimensional hexagonal pore structure, narrow pore size distribution, uniform pore distribution, and high specific surface area, can effectively improve the loading and dispersibility of the active components, thereby enhancing catalytic activity. As a result, the use of this polyolefin catalyst in olefin polymerization reactions can achieve a significantly improved conversion rate of reaction feedstocks, a higher bulk density of the obtained polymer, and further improvement in the molecular weight distribution of the obtained polyolefin product.
[0073] The raw materials used in the specific embodiments of this invention are commercially available.
[0074] The present invention will be described in detail below through embodiments.
[0075] In the following examples and comparative examples, the triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene was purchased from Aldrich, abbreviated as P123, with the molecular formula EO. 20 PO 70 EO 20 The substance with the US Chemical Abstracts Registry number 9003-11-6 has an average molecular weight Mn of 5800.
[0076] Test method:
[0077] In the following examples and comparative examples, X-ray diffraction analysis was performed on a Bruker AXS D8 Advance X-ray diffractometer (Germany); the morphology of the catalyst support was determined using a SL-30 field emission environmental scanning electron microscope (FEI, USA); pore structure parameters were analyzed using an ASAP2020-M+C adsorption analyzer (Micromeritics, USA), and the specific surface area and pore volume of the samples were calculated using the BET method; particle size distribution was measured using a MASTERSIZE particle size analyzer with n-hexane as the dispersant, with a measurement range of 0.02-2000 μm; the titanium content in the catalyst was determined using a Spectrumlab 752s UV-Vis spectrophotometer; the magnesium content in the catalyst was determined using chemical titration; the melt index of the polyolefin was determined using the method specified in ASTM D1238-99; and the bulk density was determined according to the method specified in ASTM D1895-69.
[0078] Spray drying was carried out on an LPG100 centrifugal spray dryer purchased from China Textile Group.
[0079] Example 1
[0080] This embodiment is used to illustrate the catalyst prepared using the preparation method of the present invention.
[0081] (I) Preparation of spherical sepiolite-clay mineral composite carrier:
[0082] (a) Mesoporous material filter cake No. 1: 1.0 g of triblock copolymer polyethylene glycol-polyglycerol-polyethylene glycol (Aldrich, P123) and 1.69 g of ethanol were added to 28 mL of a buffer solution of acetic acid and sodium acetate (pH = 4.4). The mixture was stirred at 15 °C until polyethylene glycol-polyglycerol-polyethylene glycol was completely dissolved. Then, 6 g of trimethylpentane was added to the above solution. After stirring at 15 °C for 8 hours, 2.13 g of tetramethoxysilane was added to the above solution. After stirring at 15 °C for 20 hours, the solution was transferred to a polytetrafluoroethylene-lined reactor and crystallized in an oven at 60 °C for 24 hours. After filtration and washing with distilled water, mesoporous silica filter cake No. 1 was obtained.
[0083] Mesoporous material filter cake No. 2: Hexadecyltrimethylammonium bromide and tetraethyl orthosilicate were added to an ammonia solution. The amount of tetraethyl orthosilicate added was 1 gram. The molar ratio of tetraethyl orthosilicate: hexadecyltrimethylammonium bromide: ammonia (25%): deionized water was 1:0.37:2.8:142. Ammonia and hexadecyltrimethylammonium bromide were added sequentially and stirred at 80°C until dissolved. The solution was filtered to obtain mesoporous material filter cake No. 2.
[0084] (b) A water glass solution with a concentration of 15% by weight and a sulfuric acid solution with a concentration of 12% by weight were reacted for 1.5 hours at a water glass: sulfuric acid weight ratio of 5:1. The pH was adjusted to 3 with sulfuric acid with a concentration of 98% by weight. The reaction material was then filtered and washed with distilled water until the sodium ion content was 0.02% by weight to obtain a silica gel filter cake.
[0085] (c) The 20g spherical mesoporous silica filter cake (10g of mesoporous material filter cake No. 1 and 10g of mesoporous material filter cake No. 2), 20g silica gel filter cake, and 20g sepiolite clay mineral prepared above were placed together into a 100mL ball mill jar. The ball mill jar was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3mm, the number of grinding balls was 1, and the rotation speed was 400r / min. The ball mill jar was sealed, and the mixture was ball milled at 60℃ for 1 hour to obtain 60g of solid powder.
[0086] (d) The solid powder was dissolved in 100 g of deionized water and spray-dried at 200 °C and 12000 r / min. The product obtained after spray drying was calcined in a muffle furnace at 500 °C for 24 hours to remove the template agent, resulting in 60 g of the target product spherical sepiolite clay mineral composite carrier with the template agent removed, thus obtaining mesoporous molecular sieve A1. Then, the product with the template agent removed was calcined at 400 °C for 10 h under nitrogen protection to perform thermal activation treatment, removing the hydroxyl groups and residual water of the mesoporous material, thus obtaining thermally activated mesoporous material B1.
[0087] Under nitrogen protection, 10g of the above-mentioned thermally activated mesoporous material B1 and 3mL of dichlorodimethylsilane were placed in a 100mL ball mill jar. The ball mill jar was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15mm, the number of grinding balls was 30, the rotation speed was 400r / min, and the ball mill was carried out at 25℃ for 20h under nitrogen protection to obtain about 10g of clay sepiolite mesoporous material carrier C1 with a particle diameter of 1-10μm.
[0088] The carrier comprises a mesoporous material and clay sepiolite loaded on the mesoporous material, and based on the total weight of the carrier, the content of the mesoporous material is 33% by weight, the content of silica gel is 33% by weight, and the content of clay sepiolite is 33% by weight.
[0089] (II) Preparation of polyolefin catalysts
[0090] (1) Add 45 mmol of magnesium dichloride, 100 mL (1.24 mol) of tetrahydrofuran, and 9.8 mmol of ethylene glycol monobutyl ether to a glass reactor equipped with a stirrer that has been purged with N2 and kept under N2 atmosphere. Then heat the reactor to 70°C and stir until a transparent solution is formed.
[0091] (2) Cool the transparent solution obtained in step (1) to 25°C, add 6.0g of mesoporous material C1 to it, stir at 50°C for 1 hour to obtain a suspension;
[0092] (3) Add 9.8 mmol of titanium tetrachloride to the suspension obtained in step (2). After the addition is complete, stir the mixture at 70°C for 1 hour to obtain the slurry to be sprayed.
[0093] (4) Under N2 protection, spray drying was carried out in a BUCHI B-290 type closed-loop airflow spray dryer (inlet temperature is 140℃, outlet temperature is 105℃, carrier gas flow rate is 360L / h, and feed rate of the slurry to be sprayed is 7mL / min) to obtain solid free-flowing powdered polyolefin catalyst Cat-1.
[0094] The clay sepiolite mesoporous material support C1 and the polyolefin catalyst Cat-1 were characterized using scanning electron microscopy and nitrogen adsorption.
[0095] In the catalyst Cat-1 obtained in this embodiment, the content of the clay sepiolite mesoporous material carrier is 90% by weight, and the content of magnesium is 7.25% by weight and the content of titanium is 2.16% by weight.
[0096] Figure 1 The X-ray diffraction pattern is used for detection, where the horizontal axis is 2θ (°) and the vertical axis is intensity. a represents the spherical sepiolite-clay mineral composite carrier (MBQGJHP). From the XRD pattern, it can be clearly seen that the mesoporous molecular sieve A1 (spherical sepiolite-clay mineral composite carrier) has diffraction peaks in the small-angle region, indicating that the mesoporous molecular sieve A1 has the two-dimensional ordered hexagonal channel structure unique to mesoporous materials.
[0097] Figure 2 These are SEM images of the microstructure of the polyolefin catalyst support. Figure 2 As can be seen from the microscopic morphology of the polyolefin catalyst support, it is spherical with a particle size in the micrometer range.
[0098] Figure 3 These are SEM images of spherical sepiolite-clay mineral composite supports (MBQGJHP-HP) loaded with phosphoric acid using a spray-drying method. Figure 3 It can be seen that the sample is spherical.
[0099] Figure 4 This is a magnified SEM image of the microstructure of a spherical sepiolite-clay mineral composite carrier (MBQGJHP) loaded with phosphoric acid via spray drying. Figure 4 It can be seen that the sample is spherical.
[0100] Figure 5 This is the pore size distribution curve of the spherical sepiolite composite carrier (MBQGJHP), from... Figure 5 It can be seen that the sample has a dual-pore distribution.
[0101] Table 1 shows the pore structure parameters of clay sepiolite mesoporous material support C1 and polyolefin catalyst Cat-1.
[0102] Table 1
[0103] sample <![CDATA[Specific surface area (m 2 / g)]]> Pore volume (mL / g) Average pore size (nm) Carrier C1 229 0.9 3;7;30 Catalyst Cat-1 182 0.3 2;5;22
[0104] As can be seen from the data in Table 1, the specific surface area and pore volume of the clay sepiolite mesoporous material carrier C1 decreased after loading magnesium and titanium components. This indicates that magnesium and titanium components entered the interior of the clay sepiolite mesoporous material carrier C1 during the loading reaction process.
[0105] (III) Catalyst Evaluation:
[0106] 1 L of hexane, 1 mmol of triethylaluminum, and 20 mg of the above catalyst components were added to a 2 L stainless steel stirred tank. The temperature was then raised to 75 °C, and hydrogen gas was added at 0.18 MPa. After hydrogenation, ethylene gas was added at 0.75 MPa, and the temperature was raised to 85 °C for polymerization. After 2 hours of reaction, the addition of ethylene was stopped, the temperature was lowered, the pressure was released, the polyethylene powder was weighed, and the catalyst activity was calculated. The bulk density of the polyethylene powder was tested, and the polymerization evaluation results are shown in Table 3.
[0107] Example 2
[0108] This embodiment is used to illustrate the catalyst prepared using the preparation method of the present invention.
[0109] (I) Preparation of carrier: Spherical sepiolite clay mineral composite carrier was prepared according to the same method as in Example 1.
[0110] (II) Preparation of polyolefin catalysts
[0111] The polyolefin catalyst was prepared according to the method of Example 1, except that the amounts of magnesium dichloride, tetrahydrofuran, ethylene glycol monobutyl ether and titanium tetrachloride were adjusted such that the content of the clay sepiolite mesoporous material support in the catalyst Cat-2 obtained in this example was 90% by weight, and the content of magnesium was 6.95% by weight and the content of titanium was 2.18% by weight.
[0112] The catalyst was evaluated in the same way as in Example 1, and the polymerization evaluation results are shown in Table 3.
[0113] Table 2 shows the pore structure parameters of clay sepiolite mesoporous material carrier C2 and polyolefin catalyst Cat-2.
[0114] Table 2
[0115] sample <![CDATA[Specific surface area (m 2 / g)]]> Pore volume (mL / g) Average pore size (nm) Carrier C2 585 1.0 4,8,30 Catalyst Cat-2 561 0.6 2.5,7,25
[0116] As can be seen from the data in Table 2, the specific surface area and pore volume of the clay sepiolite mesoporous material carrier C2 decreased after loading magnesium and titanium components, indicating that magnesium and titanium components entered the interior of the mesoporous material carrier C2 during the loading reaction process.
[0117] Example 3
[0118] This embodiment is used to illustrate the catalyst prepared using the preparation method of the present invention.
[0119] The catalyst component was prepared according to the method of Example 1, except that the ethylene glycol monobutyl ether in catalyst preparation step (1) was replaced with 13.8 mmol instead of 9.8 mmol. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 3.
[0120] Example 4
[0121] This embodiment is used to illustrate the catalyst prepared using the preparation method of the present invention.
[0122] The catalyst component was prepared according to the method of Example 1, except that 9.8 mmol of ethylene glycol monobutyl ether in catalyst preparation step (1) was replaced with 9.8 mmol of propylene glycol monomethyl ether.
[0123] The catalyst was evaluated in the same manner as in Example 1, and the polymerization results are shown in Table 3.
[0124] Example 5
[0125] This embodiment is used to illustrate the catalyst prepared using the preparation method of the present invention.
[0126] The catalyst component was prepared according to the method of Example 1, except that 100 mL of tetrahydrofuran in catalyst preparation step (1) was replaced with 130 mL (1.60 mol) of tetrahydrofuran. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 3.
[0127] Example 6
[0128] This embodiment is used to illustrate the catalyst prepared using the preparation method of the present invention.
[0129] The catalyst component was prepared according to the method of Example 1, except that 9.8 mmol of ethylene glycol monobutyl ether in catalyst preparation step (1) was replaced with 15 mmol of propylene glycol monobutyl ether. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 3.
[0130] Comparative Example 1
[0131] (1) Add 45 mmol magnesium dichloride, 120 mL tetrahydrofuran, and 9.8 mmol titanium tetrachloride sequentially to a glass reactor equipped with a stirrer and which has been purged with N2 and maintained under N2 atmosphere. Heat the reactor to 70°C and stir until a transparent solution is formed.
[0132] (2) Cool the transparent solution obtained in step (1) to 50°C, and add 6.0g of fumed hydrophobic silica (Cabot Corporation TS-610, particle size 0.02-0.1 μm, specific surface area 10m²). 2 / g, pore volume 0.1mL / g, most probable pore size 0.1nm, purchased from Cabot Corporation, USA) Stirred for 1 hour to obtain a suspension;
[0133] (3) Under N2 protection, spray drying was carried out in a BUCHI B-290 type closed-loop airflow spray dryer (inlet temperature is 140℃, outlet temperature is 105℃, carrier gas flow rate is 360L / h, and feed rate of the slurry to be sprayed is 7mL / min) to obtain solid free-flowing powdered polyolefin catalyst.
[0134] The catalyst evaluation was the same as in Example 1. The polymerization reaction results are shown in Table 3, and the catalyst scanning electron microscopy test results are shown in Table 4. Figure 2 ,from Figure 2 It can be seen that the sample is spherical.
[0135] Comparative Example 2
[0136] (1) Add 45 mmol magnesium dichloride, 120 mL tetrahydrofuran, 9.8 mmol titanium tetrachloride, and 9.3 mmol epichlorohydrin sequentially to a glass reactor equipped with a stirrer and which has been purged with N2 and kept under N2 atmosphere. Heat the reactor to 70°C and stir until a transparent solution is formed.
[0137] (2) Cool the transparent solution obtained in step (1) to 50°C, add 6.0g of fumed hydrophobic silica (Cabot Corporation TS-610, particle size 0.02-0.1 micrometers) to it, stir and react for 1 hour to obtain a suspension;
[0138] (3) Under N2 protection, spray drying was carried out in a BUCHI B-290 type closed-loop airflow spray dryer (inlet temperature is 140℃, outlet temperature is 105℃, carrier gas flow rate is 360L / h, and feed rate of the slurry to be sprayed is 7mL / min) to obtain solid free-flowing powdered polyolefin catalyst.
[0139] The catalyst was evaluated in the same manner as in Example 1, and the polymerization results are shown in Table 3.
[0140] Comparative Example 3
[0141] The polyolefin catalyst was prepared according to the method of Example 1, except that 9.8 mmol of ethylene glycol monobutyl ether was not added in step 2 of the catalyst preparation. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 3.
[0142] Comparative Example 4
[0143] The polyolefin catalyst was prepared according to the method of Example 1, except that the mesoporous material was replaced with Cabot Corporation TS610 microspheres in step 2 of Example 1. The catalyst was evaluated as in Example 1, and the polymerization results are shown in Table 3.
[0144] Table 3
[0145]
[0146] (Where, BD: bulk density; melt flow ratio: MI21.6 / MI2.16)
[0147] As can be seen from the experimental data of the examples and comparative examples in Table 3, while maintaining a high level of catalyst activity, the polymer packing density is high, the polymer melt flow ratio is small, reflecting a narrow polymer molecular weight distribution. Figure 1 , Figure 2 As can be seen from the comparison, compared with the comparative catalyst, the catalyst of the present invention has a spherical particle shape, uniform particle size, good sphericity, and good dispersibility.
[0148] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A catalyst, said catalyst comprising a support and an active component supported on said support, characterized in that, The carrier is a clay sepiolite mesoporous material carrier, the active components are magnesium and titanium components, and the average particle diameter of the carrier is 20-50 micrometers, the specific surface area is 150-600 square meters / gram, the pore volume is 0.5-1.5 milliliters / gram, and the most probable pore sizes are 2-4, 5-15, and 10-40 nanometers, respectively.
2. The catalyst according to claim 1, wherein, The specific surface area of the carrier is 180-600 square meters / gram, and the pore volume is 0.8-1.3 milliliters / gram; And / or, the most probable pore sizes of the carrier are 3-4, 7-15 and 30-40 nanometers, respectively.
3. The catalyst according to claim 1 or 2, wherein, Based on the total weight of the catalyst, the content of the clay sepiolite mesoporous material carrier is 20-90% by weight, preferably 20-70% by weight; the content of the magnesium component, calculated as elemental magnesium, is 1-50% by weight, preferably 1-30% by weight; the content of the titanium component, calculated as elemental titanium, is 1-50% by weight, preferably 1-30% by weight.
4. The catalyst according to any one of claims 1-3, wherein, The carrier comprises a mesoporous material and clay sepiolite loaded on the mesoporous material, and based on the total weight of the carrier, the content of the mesoporous material is 1-90% by weight and the content of the clay sepiolite is 1-10% by weight.
5. The catalyst according to claim 1 or 4, wherein, The method for preparing the carrier includes: (a) In the presence of a template agent, trimethylpentane and ethanol, tetramethoxysilane was first contacted with an acidic aqueous solution, and the mixture obtained after the first contact was crystallized, washed and filtered to obtain mesoporous material filter cake No. 1; hexadecyltrimethylammonium bromide and silicon source were added to an ammonia aqueous solution and filtered to obtain mesoporous material filter cake, and the filter cake was washed to obtain mesoporous material filter cake No. 2; (b) The water glass was brought into contact with the inorganic acid for a second time, and the mixture obtained after the second contact was washed and filtered to obtain a silica gel filter cake; (c) Ball mill the No. 1 mesoporous material filter cake, the No. 2 mesoporous material filter cake, the silica gel filter cake and the sepiolite clay mineral together; (d) The solid powder obtained from (c) is prepared into a slurry in the presence of deionized water and then spray-dried; and the spray-dried product is heated to remove the template agent, thereby obtaining a clay sepiolite mesoporous material carrier.
6. The catalyst according to claim 5, wherein, In step (c), the weight ratio of the sepiolite clay mineral to the No. 1 mesoporous material filter cake, the No. 2 mesoporous material filter cake, and the silica gel filter cake is (1-30):(1-30):(1-30):
20.
7. A method for preparing a catalyst, characterized in that, The preparation method includes: (1) Magnesium compounds, alcohol ether compounds and ether compounds are reacted to form a magnesium compound solution; (2) The magnesium compound solution is reacted with the clay sepiolite mesoporous material carrier in a first contact reaction to obtain a slurry; (3) The slurry is reacted with the titanium compound in a second contact reaction to obtain the masterbatch to be sprayed; (4) The masterbatch to be sprayed is spray-dried to obtain the catalyst.
8. The preparation method according to claim 7, wherein, The magnesium compound is selected from the formula Mg(OR1). m Cl 2-m One or more of the compounds shown, wherein R1 is C2-C 20 Alkyl or C3-C 20 Cyclic hydrocarbon groups, preferably C2-C 10 Alkyl groups, 0 ≤ m ≤ 2; Preferably, the magnesium compound is selected from at least one of magnesium diethoxy, magnesium dipropoxy, magnesium dibutoxy, magnesium dioctyloxy, and magnesium dichloride; And / or, the titanium compound is selected from one or more titanium halides, preferably titanium chloride and / or titanium bromide, more preferably titanium trichloride and / or titanium tetrachloride; And / or, the alcohol ether compound is selected from low carbon alcohol ethers of ethylene glycol and / or low carbon alcohol ethers of propylene glycol, preferably from one or more of propylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol monopropyl ether, propylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monobutyl ether and propylene glycol monopropyl ether. And / or, the ether compound is selected from one or more of anisole, phenethyl ether, propyl ether, butyl ether, isopropyl ether, isobutyl ether, 1,4-dioxane, tetrahydrofuran, methyltetrahydrofuran, ethylene oxide, 1,2-epoxypropane, 1,2-epoxybutane, cis-2,3-epoxybutane, trans-2,3-epoxybutane, 9,9-(dimethoxymethyl)fluorene, isopentyl ether, and pentylene ether.
9. The preparation method according to claim 7, wherein, The amount of the clay sepiolite mesoporous material carrier is 0.01-1 mol, preferably 0.02-0.9 mol, more preferably 0.03-0.8 mol; the amount of the titanium compound is 1-15 mmol, preferably 2-14 mmol, more preferably 3-10 mmol; the amount of the magnesium compound is 1-100 mmol; the amount of the ether compound is 1-10 mol; and the amount of the alcohol ether compound is 1-15 mmol.
10. The preparation method according to claim 7, wherein, In step (1), the reaction temperature is 30-100℃, preferably 40-80℃; And / or, in step (2), the temperature of the first contact reaction is 0-100°C, preferably 0-80°C; the first contact reaction time is 0.5-10h, preferably 0.5-4h; And / or, in step (3), the temperature of the second contact reaction is 0-80°C, preferably 20-70°C; the second contact reaction time is 0.5-10h, preferably 0.5-5h; And / or, in step (4), the conditions for spray drying are: inlet temperature of 100-200℃, preferably 120-160℃; outlet temperature of 60-130℃, preferably 90-115℃.
11. A catalyst prepared by the preparation method according to any one of claims 7-10.
12. The use of a catalyst according to any one of claims 1-6 and 11 in an ethylene polymerization reaction.